Kepuasan Pasien Berbasis Inovasi Pengalaman pada Fasilitas Pelayanan Kesehatan Gigi dan Mulut di Jawa Barat - Pri Agung Danarahmanto; Supriyadi Supriyadi; Julia Famor Pratami (Journal of Management and Business Review, 2022)
The healthcare industry in Indonesia continues to grow, but the health industry has a low level of resilience. This study aims to elaborate on the relationship between digital customer experience, innovation, and patient satisfaction at West Java's special dental and oral health care facilities. Data was collected using a survey of 100 patients spread across West Java. Then, the data were analyzed using path analysis and regression. The results reveal that combining digital customer experience and innovation has a significant positive role in achieving patient satisfaction. There is an influence between digital customer experience and patient satisfaction, while there is no significant effect between digital customer experience and patient satisfaction. Novelty is obtained by testing and analyzing the relationship between innovation, digital patient experience, patient satisfaction in one model, and the use of health service facilities in West Java as a unit of research analysis.